PENGAMBILAN KEPUTUSAN ETIS TOKOH UTAMA ATAS TINDAKAN EUTHANASIA DALAM NOVEL NOTHING LASTS FOREVER KARYA SIDNEY SHELDON - TALENGGORAN, BRILIANTE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Under the title â€œThe Acceptance of Main Characterâ€™s Ethical Decision Making in Performing Euthanasia in Sidney Sheldonâ€™s Nothing Lasts Foreverâ€ this study discussed about the main character, dr. Taylorâ€™s reasoning of her ethical decision making in performing euthanasia and its acceptance by the other characters. Dr. Taylor was accused murdering her own patient for a million dollar and they took her to the trial. Through the examination of character and plot, this study concludes that the intrinsic elements form the organic unity to reach the theme. This study intends to reveal the evidences from within the text, that make the main characterâ€™s action on her ethical decision making, acceptable by the society in the novel through its formal elements. The writer used descriptive method to describe the data which was taken from the novel itself. The data is analyzed using the New Criticism theory to form organic unity. In terms of characterization was based on Soemardjo and in terms of plot analysis was based on Danziger and Johnson. The findings show that there are underlying reasons of main characterâ€™s ethical decision making in performing euthanasia. Dr. Taylorâ€™s characterization proved that she was a woman physician who held humanity in the high esteem. Besides, there are some events in Embarcadero County Hospital related to the life and death crisis which support her action in making ethical decision toward her euthanized patient. Finally, it is found that there are four characters who represent the societyâ€™s acceptance of her ethical decision making in performing euthanasia and release her from an accusation of a cold-blooded killer. Keywords: ethical decision making, euthanasia, new criticism.